2016
DOI: 10.1007/s00259-016-3441-2
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT heterogeneity quantification through textural features in the era of harmonisation programs: a focus on lung cancer

Abstract: No significant difference was observed between any of the metrics considered (SUV or heterogeneity features) extracted from OSEM and PSF7 reconstructions. Furthermore, the distributions of TF for OSEM and PSF7 reconstructions according to tumour volumes were similar for all ranges of volumes.Conclusion: PSF reconstruction with Gaussian filtering chosen to meet harmonizing standards resulted in similar SUV values and heterogeneity information, compared to OSEM images, which validates its use within the harmoniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
5
26
0
Order By: Relevance
“…The quantification of heterogeneity is dependent on PET data resolution, and PSF‐corrected images are known to provide parameters with wider ranges of variation than noncorrected images. This is due to better resolution recovery and a slightly lower signal to noise ratio, which directly affect the textural information contained in the image . Our results tend to demonstrate that the textural features extracted from smoothed images remain highly correlated with those extracted from nonsmoothed images and that their prognostic pertinence is robust to image resolution in a range of low to moderate postsmoothing levels.…”
Section: Discussionmentioning
confidence: 52%
“…The quantification of heterogeneity is dependent on PET data resolution, and PSF‐corrected images are known to provide parameters with wider ranges of variation than noncorrected images. This is due to better resolution recovery and a slightly lower signal to noise ratio, which directly affect the textural information contained in the image . Our results tend to demonstrate that the textural features extracted from smoothed images remain highly correlated with those extracted from nonsmoothed images and that their prognostic pertinence is robust to image resolution in a range of low to moderate postsmoothing levels.…”
Section: Discussionmentioning
confidence: 52%
“…Other parameters such as injected activity, time per bed position, field of view could have likewise influenced the radiomic signature in favor of G2 PET device. An independent validation group will be necessary to strengthen the validity of this signature, but the modernization of PET scanners and the standardization of acquisition protocols through accreditations such as the EARL (European Association of nuclear medicine Research Ltd) FDG-PET/CT proposed by the European Association of Nuclear Medicine (EANM) are encouraging for performing multi-center PET radiomic studies such as suggested by Lasnon et al [34]. …”
Section: Discussionmentioning
confidence: 99%
“…However, because MATV [43] and most textural features [44] are sensitive to PET reconstruction parameters, attention should be paid to the PET systems used before pooling data from different centres [45]. …”
Section: Recommendations On Data Gatheringmentioning
confidence: 99%